Socio Economic Impact of Small Dams on Local Vicinity: A Case Study of Aza Khel Dam Peshawar (Global Journal of Management and Business Research, 2013)
An attempt is made in this study to evaluate the impact of Mattani Aza Khel Dam on the crop revenues, agriculture practices and overall socio-economic conditions of the area. Primary data regarding household characteristics and farm related data were collected though pre-tested interview schedule while secondary data was collected from printed documents such as PC-I, PC-IVs, progress reports, Development Statistics etc. After construction of dam in the study area, the crop revenue has significantly increased. The traditional cropping pattern has been shifted to the market oriented crops while yield of almost every crop has been improved. The number of livestock has also been increased. The water table has improved and wells were recharged as before dam construction, people were facing acute shortages of water for domestic use.
Keywords: impact evaluation study; socio-economic conditions; small dams; khyber pakhtunkhwa